Motor development in premature infants: Study protocol for an interdisciplinary hospital-home intervention - Carolina Sandoval-Cuellar; Adriana Lucía Castellanos-Garrido; Angélica María Ospina Romero; Óscar Rafael Boude Figueredo; María Eugenia Serrano-Gómez; César Augusto Fuya Caro; Diana Carolina Molina Cárdenas; Erika Marlen Pinto Rosas (Elsevier, 2023)
Background: Deviations occur in the neuropsychomotor development of premature infants; early interventions minimize delay motor. This study aimed to determine the effect of an interdisciplinary hospital-home intervention addressing motor development adaptation in premature infants in Colombia in comparison with traditional interventions. Methods: This study was based on a parallel design, with two groups, namely, experimental and control. The experimental group, hospital-home intervention (HHI) performed in two settings (i.e., hospital neonatal care units and homes), and the control group, traditional intervention, (TI) performed in institutions for premature infants.The sample will be composed of 130 randomly-allocated infants, 65 in the experimental group (HHI) and 65 in the control group (TI) of moderate to late preterm infants (gestational age between 34 and 37 weeks), weighing more than or equal to 1.800 g, who are hemodynamically stable and reside in the cities of Tunja and Bogotá-Colombia recruited between 2021 and 2022.For the pre- and post-intervention assessments, the TIMPSI and the CapDMP are the instruments used to assess motor development and the degree of parents' or caregivers' knowledge about motor development. The HHI is composed of 10 intervention strategies based on stimulation of motor development, performed twice a day for 10 min for two months, in combination with calls to a mobile device, using software (Baby Motor Skills) and an instant messaging system (WhatsApp). Results: This hospital-home intervention program proposes an approach focused on the motor development of premature infants, based on sensory and motor stimulation strategies, in addition to follow-up performed at home with the use of a mobile application that improves the motor development of premature infants. Register Clinical Trial: NCT04563364. Conclusion: The HHI provides the opportunity to determine whether the individualized four-week from admission to follow up at home with parent training will improve the motor skills of premature infants.